Applying the ARRIVE Guidelines to an In Vivo Database. - Natasha A Karp; Terry F Meehan; Hugh Morgan; Jeremy C Mason; Jeremy C Mason; Andrew Blake; Natalja Kurbatova; Damian Smedley; Julius Jacobsen; Richard F Mott; Vivek Iyer; Peter Matthews; et al. (PLoS Biology)
The Animal Research: Reporting of In Vivo Experiments (ARRIVE) guidelines were developed to address the lack of reproducibility in biomedical animal studies and improve the communication of research findings. While intended to guide the preparation of peer-reviewed manuscripts, the principles of transparent reporting are also fundamental for in vivo databases. Here, we describe the benefits and challenges of applying the guidelines for the International Mouse Phenotyping Consortium (IMPC), whose goal is to produce and phenotype 20,000 knockout mouse strains in a reproducible manner across ten research centres. In addition to ensuring the transparency and reproducibility of the IMPC, the solutions to the challenges of applying the ARRIVE guidelines in the context of IMPC will provide a resource to help guide similar initiatives in the future.